2018
DOI: 10.7602/jmis.2018.21.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine Green-Fluorescent Pancreatic Perfusion-Guided Resection of Distal Pancreas in Solid Pseudopapillary Neoplasm: Usefulness and Feasibility During Pancreaticobiliary Surgery

Abstract: ICG is widely applied in real-time imaging during abdominal surgery, plastic surgery, as well as oncologic staging and treatment. A twenty-eight year-old female patient was found to have a 4.5 cm solid pseudopapillary neoplasm in the tail of the pancreas. Under ICG-fluorescent pancreatic perfusion-guidance, we easily defined the margin of the pancreatic tumor and secured the resection margin when performing laparoscopic distal pancreatosplenectomy in the patient. No clinically relevant complications, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Biopsies can be collected from the stained tumor for fluorescent histological analysis of specific tumor markers, allowing more precise diagnoses in order to determine appropriate treatment strategies (26). Indocyanine green (ICG) is commonly used for sentinel lymph node (SLN) mapping to detect metastasis, and it is also being assessed in clinical trials for improving complete surgical resection in pancreatic, breast, liver, and brain cancers (27)(28)(29)(30). This is termed photodynamic diagnostics and has also been applied in bladder cancer with Hexvix (an ALA analog) to identify masses that were initially missed by visual tumor identification during surgery (26).…”
Section: Nir-cyanine Dyesmentioning
confidence: 99%
“…Biopsies can be collected from the stained tumor for fluorescent histological analysis of specific tumor markers, allowing more precise diagnoses in order to determine appropriate treatment strategies (26). Indocyanine green (ICG) is commonly used for sentinel lymph node (SLN) mapping to detect metastasis, and it is also being assessed in clinical trials for improving complete surgical resection in pancreatic, breast, liver, and brain cancers (27)(28)(29)(30). This is termed photodynamic diagnostics and has also been applied in bladder cancer with Hexvix (an ALA analog) to identify masses that were initially missed by visual tumor identification during surgery (26).…”
Section: Nir-cyanine Dyesmentioning
confidence: 99%
“…As a preliminary form of image‐guided surgery, intraoperative ICG can help in deciding whether to carry out minimally invasive pancreatectomy. Kim et al reported that, because the pancreas is a well‐vascularized organ, intravenous ICG will accumulate in the pancreas parenchyma. As such, they documented its usefulness in distal pancreatectomy to clearly define the appropriate margin of resection in a case of solid pseudopapillary neoplasm with poor uptake of ICG.…”
Section: Merging Icg Technology In Pancreatic Surgerymentioning
confidence: 99%